Pharmacokinetic, toxicological, and molecular interaction assessment of ginger-derived phenolics for SARS-CoV-2 main protease Inhibition - Mehdi Yoosefian; Arefeh Esmaeili; Kasim Sakran Abass (Scientific Reports)
Abstract Medicinal plants are considered rich sources of bioactive compounds with potential antiviral properties. In this study, the inhibitory effects of major phenolic compounds from Zingiber officinale (ginger), including gingerol, paradol, and shogaol, were investigated against the main protease (Mpro) of SARS-CoV-2, a critical enzyme for viral replication. The three-dimensional structures of the ligands and target protein were retrieved from PubChem and the RCSB Protein Data Bank, respectively. The pharmacokinetic and toxicity profiles of the compounds were assessed using the SwissADME and ProTox-II servers, which revealed favorable ADMET characteristics and a low toxicity profile for all selected compounds. Molecular docking was conducted using AutoDock 4.2 to predict the binding affinity and interaction modes of the ligands with Mpro. Among the tested compounds, shogaol exhibited the strongest binding affinity (– 9.95 kcal/mol) and formed stable hydrogen and hydrophobic interactions with key active site residues. To validate the docking results and further explore the stability of the ligand–protein complexes under physiological conditions, molecular dynamics (MD) simulations were performed for 500 ns using the GROMACS software. The MD analysis showed that the shogaol-Mpro complex had the lowest RMSD and consistent hydrogen bonding throughout the simulation, confirming its stable binding behavior. These findings suggest that ginger-derived phenolic compounds, particularly shogaol, may serve as promising candidates for the development of novel therapeutics targeting COVID-19 main protease.